Catalyst Engineering through Heterobidentate (N–X-Type) Ligand Design for Iridium-Catalyzed Borylation - Hoque, Md Emdadul; Hassan, Mirja Md Mahamudul; Haldar, Chabush; Dey, Sayan; Guria, Saikat; Chaturvedi, Jagriti; Chattopadhyay, Buddhadeb (Synthesis, 2022)
Iridium-catalyzed C–H activation and borylation reactions operate under mild conditions that enable easy and atom-economical installation of the versatile boronate ester group in (het)arenes and alkanes. The standard catalytic system for iridium-catalyzed borylation uses [Ir(cod)(OMe)]2 as a precatalyst, a bipyridine type ligand, and B2pin2 or HBpin as the borylating agent. Initially, a bipyridine-ligated trisboryl–iridium complex is generated that enables the borylation reaction and the regioselectivity is mainly governed by the sterics of substituents present on the ring. As a result, monosubstituted and 1,2-disubstituted arenes give mixtures of isomers. Significant efforts by several research groups have overcome the selectivity issue for directed proximal C–H borylation by introducing a directing group and newly developed ligands. This short review aims to summarize recent elegant discoveries in directed C(sp2)–H and C(sp3)–H borylation by using heterobidentate ligand (P/N–Si, N–B, and N–C) coordinated iridium catalysts.1 Introduction2 Iridium-Catalyzed Directed C–H Borylation of C(sp2)–H Bonds3 Iridium-Catalyzed Directed C–H Borylation of C(sp3)–H Bonds4 Conclusions
Keywords: C–H bond activation; ligand development; directing groups; heterobidentate ligand; iridium catalyst